The Role of International Audit Organizations in the Transition to International Standards in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is written about the activities of auditing organizations in Uzbekistan and the role of international auditing standards in this regard. The articles, rights and obligations of organizations, application of international standards and several other legal decisions are mentioned in the article of the Law of the Republic of Uzbekistan "ON AUDITING ACTIVITY".